2020
DOI: 10.1021/acsami.0c11682
|View full text |Cite
|
Sign up to set email alerts
|

Optically Programmable Plateau–Rayleigh Instability for High-Resolution and Scalable Morphology Manipulation of Silver Nanowires for Flexible Optoelectronics

Abstract: The ability to engineer microscale and nanoscale morphology upon metal nanowires (NWs) has been essential to achieve new electronic and photonic functions. Here, this study reports an optically programmable Plateau−Rayleigh instability (PRI) to demonstrate a facile, scalable, and high-resolution morphology engineering of silver NWs (AgNWs) at temperatures <150 °C within 10 min. This has been accomplished by conjugating a photosensitive diphenyliodonium nitrate with AgNWs to modulate surface-atom diffusion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The resistance and conductivity of the gauze are 45 Ω and 1.2 S/cm, respectively (Supporting Information, SI, Figure S1). Notability, since the hydrogen bonding between HPMC and the gauze surface provided strong adhesion to keep the AgNWs from falling off, the resulting conductive gauze performs with great stability. ,, SI Figure S2 shows the resistances of AgNWs coated gauze and AgNWs-HPMC coated gauze, respectively. It is found that the AgNWs-HPMC coated gauze displayed a negligibly small change in resistance after ultrasonication for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance and conductivity of the gauze are 45 Ω and 1.2 S/cm, respectively (Supporting Information, SI, Figure S1). Notability, since the hydrogen bonding between HPMC and the gauze surface provided strong adhesion to keep the AgNWs from falling off, the resulting conductive gauze performs with great stability. ,, SI Figure S2 shows the resistances of AgNWs coated gauze and AgNWs-HPMC coated gauze, respectively. It is found that the AgNWs-HPMC coated gauze displayed a negligibly small change in resistance after ultrasonication for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Since the initial AgNW films contained a large amount of solvent and exhibited poor conductivity, they were dried using three different methods, namely, thermal drying, room-temperature drying, and vacuum drying. Thermal drying was conducted at 50 °C, 80 °C, and 100 °C or 120 °C for 1 min, which are typical temperatures for fabricating silver nanowire-based electrodes to avoid Plateau-Rayleigh instability [ 27 , 28 , 29 , 30 , 31 , 32 ]. Room-temperature drying and vacuum drying were conducted for 5, 10, 20, and 30 min at room temperature and low pressure using a desiccator and low-pressure vacuum pump, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to a laser, other energy sources such as cold plasma could also be used to pattern MNWs; in the plasma scanned area MNWs are transformed into disconnected nanoparticles. Recently, a facile and versatile approach capable of selectively triggering a Plateau-Rayleigh instability of AgNWs has been reported to create multiscale structures . The AgNWs were first conjugated with a photosensitive diphenyliodonium nitrate (DPIN) and spin-coated on the substrate.…”
Section: Subtractive Patterning Methodsmentioning
confidence: 99%
“…93−95 Recently, a facile and versatile approach capable of selectively triggering a Plateau-Rayleigh instability of AgNWs has been reported to create multiscale structures. 96 The AgNWs were first conjugated with a photosensitive diphenyliodonium nitrate (DPIN) and spin-coated on the substrate. With a shadow mask, the DPIN-conjugated AgNWs could decompose under UV irradiation due to the Plateau-Rayleigh instability, resulting in the breakup of AgNWs to form an insulating area.…”
Section: Subtractive Patterning Methodsmentioning
confidence: 99%